Olga Cossettini, Pioneer of the escuela nueva in Santa Fe, Argentina - Vera de Flachs, María Cristina (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2022)
Objective: This article describes the path traveled by an Argentine teacher with a long career in the province of Santa Fe: Olga Cossettini, a teacher who, along with her sister Leticia, worked for the transformation of the primary education of her time. Originality/contribution: Her biography is based on specialized bibliography, on local and national press, sources from the Cossettini Pedagogical Archive, and on her own work. This process has allowed us to get to know the character within her generation and make a comparison with the case of Córdoba. Method: the life history method allows to reconstruct, from the voice of its protagonists, the academic formation, the analysis of the intellectual production in the context and time of application of their ideas. We focus on her life and work, especially on the contributions she made. Strategies/information collection: Collection and documentary analysis. Conclusions: The experience of the sisters Olga and Leticia Cossettini, as school principal and teacher, respectively, in Rafaela and Rosario in the province of Santa Fe, Argentina, has been an active, innovative and recreational school since its inception, with an indoors and outdoors participatory dynamic called Escuela Serena.